The Trimerization of Isocyanate‐Functionalized Prepolymers: An Effective Method for Synthesizing Well‐Defined Polymer Networks. Issue 9 (28th February 2019) - Driest, Piet J.; Dijkstra, Dirk J.; Stamatialis, Dimitrios; Grijpma, Dirk W.
Abstract: For the study of polymer networks, having access to polymer networks with a controlled and well‐defined microscopic network structure is of great importance. However, typically, such networks are difficult to synthesize. In this work, a simple, effective, and widely applicable method is presented for synthesizing polymer networks with a well‐defined network structure. This is done by the functionalization of polymeric diols using a diisocyanate, and their subsequent trimerization. Using hexamethylene diisocyanate and hydroxyl‐group‐terminated poly(ε‐caprolactone) and poly(ethylene glycol), it is shown that both hydrophobic and hydrophilic poly(urethane–isocyanurate) networks with a well‐defined network structure can readily be synthesized. By using in situ infrared spectroscopy, it is shown that the trimerization of isocyanate endgroups is clearly the predominant reaction pathway of network formation, supporting the proposed mechanism and network structure. The resulting networks possess excellent mechanical properties in both the dry and in the wet state. Abstract : The synthesis of polymer networks with well‐defined network structures is of great importance. Here, a simple, effective, and widely applicable method is presented for synthesizing both well‐defined hydrophobic and hydrophilic polymer networks. The proposed mechanism for network formation, based on the trimerization of isocyanates, is supported by in situ ATR‐FTIR, extraction and thermal measurements.